The Rose Essential To Reduce Labor Pain In Active Phase Labor - Sofia Mawaddah; Jeane Iko (JURNAL KEBIDANAN, 2020)
Labor pain is pain that is caused when labor takes place starting from the first time of labor, pain occurs because of the great activity in the mother's body to push the baby out of the womb. Maternity pain should be treated with various methods so that the mother remains relaxed and does not feel excessive pain. The purpose of this study was to determine the effectiveness of rose essential oil in reducing pain in the mother during the active phase. The design of this research is Quasi Experiment using two pre-test and post-test designs. The study population was mothers who wanted parturition in independet midwife practices and with a sample of 34 respondents who were divided into 2 groups. The independent variable is rose essential oil, the dependent variable is maternal pain in the partner and the confounding variable is birth distance and parity. The statistical test in this study is the Mann Whitney test. The research instrument was the FLACC pain scale assessment sheet and the format of the filling. Statistical test results showed the value of p = 0.006 and the mean rank value of 21.85 in the group that was given rose essential oil and 13.15 in the group that was not given rose essential oil, meaning that the administration of rose essential oil was very effective than the group that was only massaged for reduction maternal pain.